The induction of cytochrome P450 2E1 by ethanol leads to the loss of synaptic proteins via PPARα down-regulation. (15th June 2017) - Na, Shufang; Li, Jie; Zhang, Huibo; Li, Yueran; Yang, Zheqiong; Zhong, Yanjun; Dong, Guicheng; Yang, Jing; Yue, Jiang
Highlights: Both p38 and ERK signaling pathways were involved in the up-regulation of CYP2E1 levels by ethanol. The alteration of CYP2E1 levels by ethanol affected PPARα mRNA and protein levels as well as the pre-and post-synaptic proteins. The activation of PPARα attenuated the inhibition of genes related with synaptic function by ethanol. Abstract: Ethanol, one of the most commonly abused substances throughout history, is a substrate and potent inducer of cytochrome P450 2E1 (CYP2E1). Our previous study showed that brain CYP2E1 was induced by chronic ethanol treatment and was associated with ethanol-induced neurotoxicity in rats. We therefore investigated the possible mechanism of brain CYP2E1 involvement in ethanol-induced neurodegeneration. Compared with the controls, chronic ethanol treatment (3.0 g/kg, i.g., 160 days) significantly increased CYP2E1 mRNA levels in the rat cortex, but the mRNA levels of peroxisome proliferator–activated receptor α (PPARα) and the pre- and post-synaptic proteins (synaptophysin, SYP, and drebrin1, DBN1) were decreased. Ethanol treatment dose-dependently induced CYP2E1 mRNA expression, and CYP2E1 overexpression exacerbated the ethanol-induced neurotoxicity. Pretreatment with p38 inhibitor (SB202190) and ERK1/2 inhibitor (U0126) attenuated the induction of CYP2E1 mRNA and protein levels by ethanol; however, no change was observed with JNK inhibitor pretreatment. Ethanol exposure or CYP2E1 overexpression significantly decreased PPARα, SYP, and DBN1 expression as indicated by the data from real-time RT-PCR, Western blotting and immunocytochemistry. The activation of PPARα by WY14643 increased the activity of the SYP and DBN1 promoters and attenuated the inhibition of these genes by ethanol. The specific siRNA for CYP2E1 significantly attenuated the ethanol-induced inhibition of PPARα, SYP and DBN1 mRNA levels. These results suggest that the induction of CYP2E1 by ethanol may be mediated via the p38 and ERK1/2 signaling pathways in neurons but not via the JNK pathway. The CYP2E1-PPARα axis may play a role in ethanol-induced neurotoxicity via the alteration of the genes related with synaptic function.